2021
DOI: 10.1177/21677026211009508
|View full text |Cite
|
Sign up to set email alerts
|

Filthiness of Immorality: Manipulating Disgust and Moral Rigidity Through Noninvasive Brain Stimulation as a Promising Therapeutic Tool for Obsessive Compulsive Disorder

Abstract: The study was designed to test the hypothesis that indirect inhibition of the insula via cathodal transcranial direct current stimulation (tDCS) would decrease disgust and moral rigidity in 36 healthy individuals undergoing 15 min of tDCS over the temporal lobe. To obtain a comprehensive assessment of disgust, we used subjective (affect rating), physiological (heart rate variability [HRV]), and implicit measures (word-fragment completion), and moral judgment was assessed by asking participants to rate the deon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Thus, it can be assumed that due to experiencing severe negative emotions, VOI was not effective when OC patients encountered personal moral dilemmas. This notion is bolstered by the findings of Salvo et al (2022) revealing that inhibition of the insula, which is responsible for emotional processing, reduces disgust and deontological judgments in OC patients. In the same vein, previous studies have shown that OC patients process self-conscious emotions (i.e., shame and guilt) differently from others (Henning-Fast et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it can be assumed that due to experiencing severe negative emotions, VOI was not effective when OC patients encountered personal moral dilemmas. This notion is bolstered by the findings of Salvo et al (2022) revealing that inhibition of the insula, which is responsible for emotional processing, reduces disgust and deontological judgments in OC patients. In the same vein, previous studies have shown that OC patients process self-conscious emotions (i.e., shame and guilt) differently from others (Henning-Fast et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The paucity of studies targeting the rAI with non-invasive brain stimulation techniques is likely due to difficulties in reaching such a deep brain region; however, secondary activations within the insular cortex have been demonstrated by combining brain stimulation and resting-state functional magnetic resonance imaging ( Li et al., 2017 ). It also appeared possible to indirectly increase cortical excitability in the insular cortex by the use of transcranial direct current stimulation (tDCS) (e.g., Petrocchi et al., 2017 ; Salvo et al., 2021 ), possibly modulating interoception ( Sagliano et al., 2019 ). TDCS functions through subthreshold modulation of the membrane potentials of neurons, by altering cortical excitability ( Nitsche & Paulus, 2000 ), ultimately changing neuronal synaptic plasticity ( Brunoni et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%